Koncepcja Dobra (tagathon) w filozofii przedplatońskiej - Pacewicz, Artur (Instytut Filozofii Uniwersytetu Wrocławskiego, 2006)
The aim of the article is to outline an interpretation of the philosophical understanding of the concept of the good in pre-Platonic thought. The interpretation is based on those fragments only in which the concept actually appears. As a result of the adopted assumption, the ideas of the ﬁrst philosophers, i.e. Thales, Anaximander and Anaximenes, were outside the scope of the investigation, as well as those ofXenophanes, Eleatics, Empedocles, Anaxagoras and Leucippus. In the case of the ﬁrst philosophical systems of the pre-Platonic philosophy, one notices a connection between the good and the One. It can also be found that understanding of the ‘the Best’ is depended on, and results from, ‘the good’. This is true also in Heraclitus, though, at the same time, he introduces a signiﬁcant reversal in this respect, for he abolishes the absolute diﬀerence between the good and evil, and turns it to a subjective relation. The good has no ontological basis in the Democritus’ system as well, though the good’s connection with truth, accessible for every human being, allows to interpret him as arguing for an objectivistic conception of the good. Theobjectivity of good has subsequently been denied by the Sophists.
Keywords: good; Presocratics; Sophists